Formation of hybrid cdse-loaded tio2 nanotubes for solar-driven photoelectrochemical water splitting process / Lau Kung Shiuh - Lau, Kung Shiuh (2016)
Solar hydrogen generation from water electrolysis is a key target for the development of sustainable hydrogen economy for future energy system. The formation of self-organized TiO2 nanotubes without bundling is essential for high efficiency in photoelectrochemical (PEC) water electrolysis application. This research project demonstrated an efficient approach to enhance the solar-driven photoelectrochemical (PEC) water splitting performance by incorporating an optimum amount of CdSe species into TiO2 nanotubes film. Based on the results obtained, highly ordered TiO2 nanotubes (AR = 57.95, G = 379.04) were successfully synthesized through electrochemical anodization of Ti foil in ethylene glycol electrolyte containing 0.3 wt% of NH4F and 5 wt% of H2O2 at 40 V for 1 h. Promising anodic TiO2 nanotubes were further underwent heat treatment at 400 °C for 4 h. Continuous efforts have been exerted to further improve the PEC water splitting performance by incorporating an optimum content of CdSe species into TiO2 nanotubes using chemical bath deposition technique. It was found that TiO2 nanotubes soaked in 5 mM CdSe precursor for one hour at room temperature exhibited higher photocurrent density (~2.50 mA/cm2) compared to pure TiO2 nanotubes (1.45 mA/cm2). The presence of CdSe at approximately 1 at% in TiO2 showed an improvement of photocurrent density because it acted as an effective mediator to trap the photo-induced electrons and minimizes the recombination of charge carriers. In contrast, excessive CdSe content of 1.5 at% loading and higher on the wall surface of TiO2 nanotubes resulted in poor PEC water splitting performance because independent layers acting as recombination centers for the charge carriers was formed.